Georgia : Poverty Reduction Strategy Paper Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
The implementation of Georgia's poverty reduction strategy has proceeded well, with impressive achievements in curbing corruption, improving the business climate, and continued improvement in public finances. Particular emphasis should be given to enhancing macroeconomic management, implementing the new legislative framework, improving the effectiveness of public expenditure policies, enhancing the efficiency of infrastructure spending, and supplementing pro-growth policies with an effective social safety net. Broadening improvements in governance by judicial reform and fostering participation of civil society in all dimensions of the reform strategy is also required.